2016
DOI: 10.1049/iet-map.2016.0069
|View full text |Cite
|
Sign up to set email alerts
|

Periodic array of complementary artificial magnetic conductor metamaterials‐based multiband antennas for broadband wireless transceivers

Abstract: This study presents the empirical results of a low-profile light-weight antenna based on a periodic array of the complementary artificial magnetic conductor metamaterial structure, which is realised by loading the antenna with Eshaped slits and inductive microstrip lines grounded using metallic via-holes. The finalised prototype antenna operates over a broadband of 0.41-4.1 GHz, which corresponds to a fractional bandwidth of 165.84%, and has dimensions of 40 × 35 × 1.6 mm 3 or 0.054l 0 × 0.047l 0 × 0.0021l 0 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…In recent years, the concept of composite right/left‐handed (CRLH)‐metamaterials (MTMs) has been extensively applied in the development of planar microstrip antennas (Ahmed et al, ; Alibakhshi‐Kenari & Naser‐Moghadasi, ; Alibakhshi‐Kenari et al, a, b, , , , ; Best, ; Caloz, ; Caloz & Itoh, ; Engheta & Ziolkowski, ; Lee et al, , ), where miniaturization and good radiation characteristics have been reported. Design of such antennas, however, include the use of via‐holes, defected ground structures, or lumped elements, which are undesirable as these artifacts introduce additional complexity in the fabrication of the antenna and hence high cost, which limits their practical use (Ahmed et al, ; Caloz, ; Engheta & Ziolkowski, ; Lee et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the concept of composite right/left‐handed (CRLH)‐metamaterials (MTMs) has been extensively applied in the development of planar microstrip antennas (Ahmed et al, ; Alibakhshi‐Kenari & Naser‐Moghadasi, ; Alibakhshi‐Kenari et al, a, b, , , , ; Best, ; Caloz, ; Caloz & Itoh, ; Engheta & Ziolkowski, ; Lee et al, , ), where miniaturization and good radiation characteristics have been reported. Design of such antennas, however, include the use of via‐holes, defected ground structures, or lumped elements, which are undesirable as these artifacts introduce additional complexity in the fabrication of the antenna and hence high cost, which limits their practical use (Ahmed et al, ; Caloz, ; Engheta & Ziolkowski, ; Lee et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the emerging notion of metamaterial with different resonator unit shapes has played a great role in reducing the complexity incurred due to the addition of extra structures and improving performance of antennas . In this section, the bandwidth enhancement techniques will be presented by categorizing them based on the placement of metamaterial structure on/near the patch, loaded/etched in the ground plane, embedded in the substrate, and as superstrate …”
Section: Applications Of Metamaterials In Antenna Engineeringmentioning
confidence: 99%
“…Metamaterial has some unusual and interesting properties, 7 which can be used for the improvement of different antenna parameters. For example, impedance bandwidth, [8][9][10][11] side-lobe levels, isolation in MIMO antennas, [12][13][14] crosspolarization, 15 antenna gain [15][16][17][18][19][20] can be improved by exploiting various properties of MTMs. In, ref.…”
Section: Introductionmentioning
confidence: 99%